2011
DOI: 10.1111/j.1600-6143.2010.03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Window Period HIV Infection in High Infectious Risk Donors: Systematic Review and Meta-Analysis

Abstract: The OPTN defines high risk donors (HRDs), colloquially known as 'CDC high risk donors' , as those thought to carry an increased risk of HIV window period (WP) infection prior to serologic detectability. However, the true risk of such infection remains unknown. To quantify the risk of WP infection in each HRD behavior category, we performed a systematic review and metaanalysis of studies of HIV prevalence and incidence. Of 3476 abstracts reviewed, 27 eligible studies of HIV infection in HRD populations were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(137 citation statements)
references
References 59 publications
1
134
0
2
Order By: Relevance
“…For recipients of PHS infectiousrisk kidneys, the estimated rates of HIV transmission are lower than those for HCV. 23,24 By comparison, the annual death rate for wait-listed patients is approximately 4% and higher for subgroups with diabetes or over 60 years of age. 25 Post-transplant patient and allograft survival appear to be similar between recipients of PHS infectious-risk versus standard criteria organs, 26 which is not surprising given the tiny predicted rates of disease transmission.…”
Section: Organ Acceptance and Risks Of Disease Transmissionmentioning
confidence: 99%
“…For recipients of PHS infectiousrisk kidneys, the estimated rates of HIV transmission are lower than those for HCV. 23,24 By comparison, the annual death rate for wait-listed patients is approximately 4% and higher for subgroups with diabetes or over 60 years of age. 25 Post-transplant patient and allograft survival appear to be similar between recipients of PHS infectious-risk versus standard criteria organs, 26 which is not surprising given the tiny predicted rates of disease transmission.…”
Section: Organ Acceptance and Risks Of Disease Transmissionmentioning
confidence: 99%
“…HIV is of greatest concern to candidates, but its risk is best described as miniscule, with transmission risk for nucleic acid test (NAT) negative donors being ≤ 0.12% across all PHS-HR categories. 4 With no documented transmission since 2013, despite an increased use of PHS-HR organs, ≤ 0.12% is likely an inflated estimate. HCV risk has variability between donor history elements with the donor discovered with needle in arm proceeding rapidly to donation thought to have a 3% risk of NAT negative transmission.…”
mentioning
confidence: 99%
“…A recent metaanalysis demonstrated that for hepatitis C, the highest risk (without NAT screening) of window period infection was 300/10,000 donors for injection drug users [43]. For window period HIV infection, the highest risk was for men who have sex with men (10.2/10,000) and intravenous drug users (12.1/10,000) [44]. Due to the increased risk of donorderived infection in OPTN-defined increased donors, routine follow-up testing for hepatitis B, hepatitis C, and HIV is indicated in this group.…”
Section: Increased Risk Deceased Donors and Recipient Follow-upmentioning
confidence: 97%